Job satisfaction and turnover under the effect of personorganization fit in Albanian public organizations - Mimoza Kasimati (Journal for East European Management Studies, 2011)
This paper presents the results of research conducted on public organizations employees for testing a model that relates person-organization fit, job satisfaction and turnover. Using a sample of 100 employees from 17 Albanian public organizations, this study brings out that there is a significant relationship between person-organization fit and job satisfaction in the public organizations in Albania. The implications of the study are discussed. – – Dieser Artikel stellt die Resultate einer Untersuchung dar, deren Gegenstand war, an Angestellte von öffentlichen Organisationen ein Modell zu erproben, welches das Harmonieren der Person mit der Organisation mit der Arbeitszufriedenheit und der Fluktuation verknüpft. Durch die Benutzung einer Stichprobe von 100 Angestellten von 17 albanischen öffentlichen Organisationen, kommt diese Studie zu dem Ergebnis, dass es eine signifikante Verbindung zwischen dem Harmonieren einer Person mit der Organisation und der Arbeitszufriedenheit in öffentlichen Organisationen in Albanien gibt. Die Konsequenzen der Studie werden diskutiert.
Keywords: 650; Person-organization fit; job satisfaction; turnover